2015
DOI: 10.1177/1024258914567427
|View full text |Cite
|
Sign up to set email alerts
|

Stepping up to strike: a union mobilization case study of Polish migrant workers in the Netherlands

Abstract: This article examines a union mobilization of Polish temporary agency workers in the Netherlands. The case study contributes to the migrant organizing literature a micro-level account of the dynamics of mobilization from the viewpoint of the migrants and organizers involved. The findings emphasize the importance of key actors in building solidarities within and between different groups of workers in fragmented workplaces, with implications for unions seeking new ways to respond to changing employment practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 139 publications
(316 reference statements)
0
11
0
1
Order By: Relevance
“…Workplace meetings seem crucial in gaining the support of workers, even though new ICTs play a role in preparing and complementing those meetings. As some studies seem to identify, face-to-face meetings take on particular importance in workplaces with a weak or non-existent union presence (Berntsen, 2015). Furthermore, the survey carried out by Kerr and Waddington (2014) regarding the utility of the respective communication strategies attributed the highest score to the local representative.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace meetings seem crucial in gaining the support of workers, even though new ICTs play a role in preparing and complementing those meetings. As some studies seem to identify, face-to-face meetings take on particular importance in workplaces with a weak or non-existent union presence (Berntsen, 2015). Furthermore, the survey carried out by Kerr and Waddington (2014) regarding the utility of the respective communication strategies attributed the highest score to the local representative.…”
Section: Discussionmentioning
confidence: 99%
“…While this study focuses on the German setting, other studies point to similar negative labour rights when workers are posted to another EU Member State via subcontracting or temporary work agencies. Studies in the Netherlands, France and Finland have revealed similar precarious working conditions for posted workers (Berntsen, ; Lillie et al . ; Lefebvre, ).…”
Section: Mapping the Shape Of The Pan‐european Labour Marketmentioning
confidence: 81%
“…While this study focuses on the German setting, other studies point to similar negative labour rights when workers are posted to another EU Member State via subcontracting or temporary work agencies. Studies in the Netherlands, France and Finland have revealed similar precarious working conditions for posted workers (Berntsen, 2015;Lillie et al 2014;Lefebvre, 2006). Employer behaviour is fairly similar in all examined countries in the sense that firms can easily circumvent the posting framework, which is made possible by the ambiguous rule system surrounding posted workers and their work environments.…”
Section: Mapping the Shape Of The Pan-european Labour Marketmentioning
confidence: 85%
“…The literature on migrant organising has detailed many successful cases of organising and mobilising precarious migrant workers (Milkman, 2006;Berntsen, 2015;Connolly et al, 2017;Benvegnu et al, 2018). Posted workers, however, are more difficult to organise than other forms of precarious migrants.…”
Section: Migrant Worker Engagementmentioning
confidence: 99%